Agrarian Dreams: The Paradox of Organic Farming in California - Julie Guthman (University of California Press, 2014)
I completed most of the research for the first edition of Agrarian Dreams about fifteen years agoâ€”sometime in 1998â€”and then began writing the dissertation that was to become this book. When it was finally published, in 2004, there were very few scholarly publications on organic agriculture and thus a good many assumptions to call into question. The public conversation on organics was just emerging. At the time, most peopleâ€™s ideas about organic farming fell into one of two camps. They believed it to be either a weird fringe movement or the best possible alternative to conventionally produced food. Since then much has changed. Those who once saw organic as fringe are now less skeptical of the basic premise that farming ought to be done with no or fewer pesticides, although they may still harbor doubts that the organic label is more than a marketing ploy. They may even buy organic food from time to time, especially those with young children or with a lively farmersâ€™ market nearby. Meanwhile, those who were once inclined to believe that organic agriculture was a substantial path to agrofood transformation have become more wary. Theyâ€™ve seen organic food at large grocery stores side by side with conventional brands and are skeptical that it is a substantial alternative. Perhaps theyâ€™ve read Michael Pollanâ€™s Omnivoreâ€™s Dilemma, which pop - ularized the juxtaposition of â€œbig organicâ€ and â€œlittle organic,â€ and now seek an even more rarefied alternative, such as local food. Of those in this camp who are deeply immersed in food activismâ€”a small but vocal, agenda-setting groupâ€”some have come to doubt that market approaches to food system transformation will work at all and have moved on to other iterations of â€œalternative food movements,â€ whether food justice, urban agriculture, or, most recently, food sovereignty.